The relationship between isometric strength and sprint acceleration in sprinters - Brady, C. J.; Harrison, A. J.; Flanagan, E. P.; Haff, G. G.; Comyns, T. M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the relationships between the isometric midthigh pull (IMTP), isometric squat (ISqT), and sprint acceleration performance in track-and-field sprinters and to determine whether there are differences between men and women. Methods: Fifteen male and 10 female sprinters performed 3 maximal-effort IMTPs, ISqTs, and 3?30-m sprints from blocks. Results: Among the men, the results showed significant negative correlations between IMTP and ISqT peak force; relative peak force; force at 100, 150, and 200 ms; rate of force development (0-150 and 0-200 ms); and impulse (0-200 ms) and 0- to 5-m time (r=-.517 to -.714; P<.05). IMTP impulse (B=-0.582, P=.023) and ISqT relative peak force (B=-0.606, P?=?.017) significantly predicted 0- to 5-m time. Among the women, no IMTP or ISqT variables significantly correlated with any sprint times. Men measured significantly higher than women for all IMTP measures except relative peak force. Men were significantly faster than women at all splits. When comparing measures of the ISqT, there were no significant differences between men and women. Conclusions: Variables measured during the IMTP and ISqT significantly correlated with 0- to 5-m sprint performance in male athletes. Isometric strength can have a sizable influence on 0- to 5-m time, but in some cases, the maximum effect could be very small.